Discourses of power in mathematics education research: concepts and possibilities for action (2008)
Mathematics education is powerful. This is an assertion that appears often in mathematics education research papers. However, the meaning of the assertion is far from being clear. An analysis of different ways of talking about power in relation to mathematics education, in research literature, is put forward. Three main discourses are identified: Power as an intrinsic capacity, power as structural imbalance, and power as distributed positioning. Identifying these discourses allows clarifying the values associated to mathematics education and the pedagogical imaginaries that are possible to envision for mathematics teaching and learning.